Air pollution and emergency department visits for epistaxis. (December 2014) - Szyszkowicz, M.; Shutt, R.; Kousha, T.; Rowe, B.H.
<x xml:space="preserve">Abstract</x> Objectives This study aimed to evaluate the association between outdoor ambient air pollution and emergency department (ED) visits for epistaxis. Design Cross‐sectional study, case–crossover design. Setting ED visit data were obtained for Edmonton, Alberta, Canada, for a period of 10 years starting 1 April 1992 and ending March 31st of 2002. The data on ED visits were supplied by Capital Health for the five major acute care hospitals in the Edmonton area. Participants The analysis was performed for the population as a whole (N = 15 038) and split by sex: males (N = 8587) and females (N = 6451). Main outcome measures We explored associations between ambient concentrations of air pollutants (CO, NO2, SO2, O3, PM10, PM2.5) lagged by 0–4 days and ED visits for epistaxis in Edmonton, Alberta, Canada. Results Odds ratios (ORs) and their 95% confidence intervals (CI) were reported for an increase in an interquartile range (IQR) of pollutant concentration. We obtained positive and statistically significant results for all patients with epistaxis; exposure to O3 with IQR = 14 ppb, OR = 1.05 (95% CI: 1.00–1.09, lag 0), and for males (age < 25 years), OR = 1.16 (1.03–1.30), lag 4; and to PM10 with IQR = 15 μg/m3, OR = 1.02 (1.00–1.05, lag 3). These results were stronger for older (age > 24 years) females. Conclusions These findings suggest that there may be an association between air pollutant exposure, specifically ozone and PM10, and the number of ED visits for epistaxis.